PKM Peningkatan Keterampilan Kelompok Wanita Tani Melalui Pembuatan Gula Semut Di Desa Bungaeja Kabupaten Gowa - Nur Rahmah; Amirah Mustarin; Reski Praja Putra; Indrayani Indrayani; Ervi Novitasari (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
This Community Service Program (PKM) was carried out as an effort to improve the knowledge and skills of the farmer women's group in Bungaejaja village, Gowa Regency. The problems found in the peasant women's group are the lack of skills of farm women and unused free time to contribute to the family's livelihood. The purpose of this community empowerment activity is to improve the skills of farmer women groups through making ant sugar, Partners will be able to know how to make good quality ant sugar by paying attention to the factors in the manufacturing process so that farm women will know the procedures and principles of making ant sugar and the characteristics of the ant sugar produced. The method applied in this activity is a descriptive method, with a lecture, discussion, and demonstration approach. The expected result of this training is that the farmer women's group can improve theoretical and practical competence in making ant sugar with good and correct manufacturing procedures and principles to produce good quality ant sugar.